Pengaruh Arus Kas Operasi, Laba Bersih dan Cash Ratio Terhadap Dividen Kas pada Perusahaan Sektor Keuangan yang Terdaftar di Bursa Efek Indonesia Periode 2020-2023 - Cici Apriliya; Rihfenti Ernayani; Butet Wulan Trifina (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to empirically determine the effect of operating cash flow, net profit and cash ratio on cash dividends in financial sector companies listed on the Indonesia Stock Exchange (IDX) in the period 2020-2023. The population of this study uses a quantitative research method with a sampling technique using purposive sampling which determines certain criteria to obtain samples, resulting in 11 companies with 97 observation data for 4 years. The data collection technique uses secondary data. The data analysis model uses SPSS version 25 which includes Linear Regression Analysis, Classical Assumption Test, Determination Test, and Hypothesis Test. The results of the study show that operating cash flow has an effect on cash dividends, net profit and cash ratio have no effect on cash dividends.